Investigation the Role of Palbociclib on Fatty Acid Synthase Metabolism through Regulation of miR-33a in Pancreatic Cancer Cells - Telci, Dilek; ARISAN, ELİF DAMLA; RENCÜZOĞULLARI, ÖZGE (My University, 2019)
Aberrant activation of fatty acid (FA) synthesis is associated with cancer development including pancreatic cancer (PC). SREBP is an important regulator of FA synthesis and modulated by growth factor signaling which is also targeted by miR-33a. We aim to determine the role of palbociclib, CDK4/6 inhibitor, on the regulation of FA synthase metabolism through targeting regulators of SREBP such as miR-33a in PC cells. The expression profiles of FA metabolism signaling axis were examined by immunoblotting. The levels of miRNA profiles were analyzed by RT-PCR. Oil red O staining determined the oil droplets in PC cells. Palbociclib exerted a controversial effect on the expression of FA synthesis signaling axis such as FASN, ACL in Panc-1 and MiaPaCa-2 cells. Palbociclib treatment increased the expression of FASN, p-ACL, and ACSL-1 in Panc-1 cells. However, the expression levels of mature SREBP2 were decreased by palbociclib treatment and overexpression of miR-33a resulted in a further decrease of precursor and mature SREBP protein levels in Panc-1 cells. Moreover, inhibition of miR-33a significantly upregulated the SREBP levels in palbociclib-treated Panc-1 cells. The content of lipid drops in Panc-1 cells was more reduced after co-treatment of miR33a with palbociclib. In conclusion, key regulatory factors of lipid metabolism such as FASN, SREBP are important targets to control PC cell proliferation. Overexpression of miR-33a decreased the level of SREBP2 which indicated the downregulation of FA metabolism. It was suggested that the effect of palbociclib on the downregulation of FA synthesis and cell viability was further increased by SREBP targeted-miR-33a.
Keywords: Pancreatic Cancer; miRNA; Palbociclib; Fatty Acid Metabolism